PSII-22 The Effects of Lactobacillus Fermentum on Sow and Litter Performance. (7th May 2021) - Knapp, Josh K; Winkel, Shana M; Bartenslager, Alison; Trenhaile-Grannemann, Melanie D; San Andres, Joice V; Nguyen, Khang; Wittler, J'Nan; Kinstler, Sydney; Fernando, Samodha; Miller, Phillip; Burkey, Thomas
Abstract: The use of probiotics may be an effective strategy in sustainable pig production. The objective of this experiment was to examine the effects of Lactobacillus fermentum LfQi6 (LF) on sow and litter performance. First parity, gestating sows (UNL Resource Population Rep x DNA Genetics Duroc; n = 28) were allotted one of two treatment groups. Treatment groups consisted of a control group (CTL) fed a standard gestation and lactation diet for the duration of the study, while the experimental group was fed CTL supplemented with 10^10 CFU LF per day from d 80 of gestation through lactation. Individual piglet body weights (BW) were recorded weekly. LF sows tended to enter the farrowing crates lighter than the control sows (209.93 vs 200.91kg; P = 0.0794). LF sows had a smaller loin eye area when compared to CTL sows (6.24 vs 5.86 cm 2 ; P = 0.0374) when entering the farrowing crates. However, LF sows tended to lose less loin area per day when in the crate (0.025 vs 0.012 cm 2 /d; P = 0.078); resulting with there being no difference in loin area when the sows left the farrowing crates. Piglet BW tended to be greater at weaning for the sows fed the LF (5.37 vs 5.66 kg, P = 0.0528). The mean piglet BW were 1.25, 1.33; 2.37, 2.44; 4.08, 4.22; and 5.37, 5.66 at d 0, 7, 14, 21; respectively for CTL and LF. Sows fed the LF had fewer pigs born alive per litter (16.09 vs 14.12; P < 0.05) when compared to the sows fed the control diet. However, piglet mortality tended to be decreased for LF compared to CTL (3 vs 1.76; P = 0.0645). Results suggest that supplementation with Lactobacillus fermentum LfQi6 may provide some benefits with respect to sow and litter performance.